ANALYSIS OF NETWORK SECURITY PROBLEMS AND SOLUTIONS FOR MACHINE TO MACHINE COMMUNICATIONS - KARABADE, ABUBAKAR (Fırat Üniveristesi, 2016)
The M2M communication is a rapidly developing large scale networking device which exchanges information and services without human intervention. M2M communication plays a significant role in many applications includes healthcare, smart house, telemetry and intelligent transportation system, etc. creating billions of devices connected to each other virtually and physically through the Internet. In addition, M2M communication supports the development of smart applications that will enhance the demand of people on how to live, work, and exchange information. Due to the low cost, deployment nature, unguarded, huge number of devices and lack of secure standardization, M2M communication network has several security challenges. These security challenges include Sybil attack, DDoS, falsification attack, etc. Therefore, the intruders try to compromise the credential of network using malware programs and prevent devices from getting services. In order to secure M2M communication network, these security challenges need to be fully addressed to provide confidentiality, availability, integrity and service authentication. In this thesis, we present the analysis of network security problem for M2M communication using OMNET++ simulator and INET simulation model. The analysis is carried out in terms of end-to-end delay, network throughput, sinkhole attack, energy consumption and quality of services (QoS). This thesis also discusses M2M communication technologies, network security problem, and common existing security solution for M2M communication. In addition, we performed the analysis comparison between the normal network topology and network topology that under attacks. The simulation result shows that when M2M communication network no countermeasure is taken into account, the network can be easily compromised and degrade in its performance.

The M2M communication is a rapidly developing large scale networking device which exchanges information and services without human intervention. M2M communication plays a significant role in many applications includes healthcare, smart house, telemetry and intelligent transportation system, etc. creating billions of devices connected to each other virtually and physically through the Internet. In addition, M2M communication supports the development of smart applications that will enhance the demand of people on how to live, work, and exchange information. Due to the low cost, deployment nature, unguarded, huge number of devices and lack of secure standardization, M2M communication network has several security challenges. These security challenges include Sybil attack, DDoS, falsification attack, etc. Therefore, the intruders try to compromise the credential of network using malware programs and prevent devices from getting services. In order to secure M2M communication network, these security challenges need to be fully addressed to provide confidentiality, availability, integrity and service authentication. In this thesis, we present the analysis of network security problem for M2M communication using OMNET++ simulator and INET simulation model. The analysis is carried out in terms of end-to-end delay, network throughput, sinkhole attack, energy consumption and quality of services (QoS). This thesis also discusses M2M communication technologies, network security problem, and common existing security solution for M2M communication. In addition, we performed the analysis comparison between the normal network topology and network topology that under attacks. The simulation result shows that when M2M communication network no countermeasure is taken into account, the network can be easily compromised and degrade in its performance.
Keywords: Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol